2018
DOI: 10.1186/s13002-018-0225-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomycological study in the Kilum-Ijim mountain forest, Northwest Region, Cameroon

Abstract: BackgroundMajority of the people in rural areas depend on traditional fungi-based medicines to combat different illnesses. This ethnomycological survey was undertaken to document the traditional knowledge of mushrooms among the communities in the Kilum-Ijim mountain forest reserve. Although macrofungi are exploited for food and medicine, their ethnomycological knowledge has not been documented in this ecosystem.MethodsA field study was carried out between 2014 and 2015; 14 mushrooms used by the local communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 28 publications
8
36
0
3
Order By: Relevance
“…For example, Trametes elegans and Trametes hisurta were evolutionary related to species from Cameroon previously reported by Douanla-Meli (2007) from the Mbalmayo Forest Reserve, Trametes elegans had been reported by Kinge et al (2013) in the Mount Cameroon Region specifically in the localities of Idenau, Bafia and Ekona. Trametes sanguinea and Trametes hirsuta found in this study had been reported by Teke et al (2017) on macro fungal diversity in the Kilum-Ijim forest, Cameroon. In this study Trametes sanguinea was related to species from U.S.A. Favolus acervatus was related to species from China.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…For example, Trametes elegans and Trametes hisurta were evolutionary related to species from Cameroon previously reported by Douanla-Meli (2007) from the Mbalmayo Forest Reserve, Trametes elegans had been reported by Kinge et al (2013) in the Mount Cameroon Region specifically in the localities of Idenau, Bafia and Ekona. Trametes sanguinea and Trametes hirsuta found in this study had been reported by Teke et al (2017) on macro fungal diversity in the Kilum-Ijim forest, Cameroon. In this study Trametes sanguinea was related to species from U.S.A. Favolus acervatus was related to species from China.…”
Section: Discussionsupporting
confidence: 83%
“…This species was identified only by morphology as it is relatively easy to identify. This species was also reported to be edible by Teke et al (2018) on ethnomycological study in the Kilum-Ijim mountain forest, North West region of Cameroon. Species from the genus Microporus, Trametes and Ganoderma have also been reported to be medicinal by other authors in different ethnomycological studies.…”
Section: Journal Of Biology and Life Sciencementioning
confidence: 87%
See 1 more Smart Citation
“…Depuis des millénaires en Chine et chez les Romains, et depuis plusieurs siècles chez les communautés sédentaires Bantou et les peuples autochtones nomades des forêts humides d'Afrique centrale, les champignons sauvages comestibles (CSC) constituent d'excellentes ressources alimentaires primaires, surtout en périodes de soudure, et secondairement médicinales (Boa, 2006 ;Eyi et al, 2014). Dans ce contexte, la collecte, la consommation et l'utilisation des champignons sous-tendent des pratiques traditionnelles et culturelles très anciennes Boa, 2006 ;Teke et al, 2018). Cependant, les communautés de macrochampignons sauvages comestibles du Cameroun, qui représentent une des plus importantes sources de biodiversité alimentaire, restent faiblement valorisées et leurs connaissances peu capitalisées.…”
Section: Introductionunclassified
“…Plusieurs études ont rapporté la quantité de champignons sauvages consommés en Tanzanie et à travers le monde (Rammeloo et Walleyn, 1993 ;Härkönen et al, 1994Härkönen et al, , 2003Mueller et al, 2007). L'importance et les usages des CSC ont été décrits pour la communauté Yoruba au Nigeria, les pygmées Aka et Bofi de la République centrafricaine (Heim, 1942 ;Oso, 1975Oso, , 1977Malaisse et al, 2008), les Bantu et les Bagyeli du Cameroun (Dijk et al, 2003), les Nagots du Bénin , les communautés Bakweri du Mont Cameroun et une dizaine de communautés de la forêt montagneuse de Kilum-Ijum, au nord-ouest du Cameroun (Teke et al, 2018).…”
Section: Introductionunclassified